Nagwa uses cookies to ensure you get the best experience on our website. Learn more about our Privacy Policy.

Lesson: Partial Fraction Expansion: Repeated Linear Factors

Sample Question Videos

Worksheet • 4 Questions • 1 Video

Q1:

Express π‘₯ βˆ’ 2 ( π‘₯ + 2 ) ( π‘₯ + 1 ) 2 2 in partial fractions.

  • A 2 π‘₯ + 2 βˆ’ 1 π‘₯ + 1 βˆ’ 1 ( π‘₯ + 1 ) 2
  • B βˆ’ 2 π‘₯ + 2 βˆ’ 1 π‘₯ + 1 βˆ’ 1 ( π‘₯ + 1 ) 2
  • C βˆ’ 1 π‘₯ + 2 + 2 π‘₯ + 1 βˆ’ 1 ( π‘₯ + 1 ) 2
  • D 2 π‘₯ + 2 + 1 ( π‘₯ + 1 ) 2
  • E 2 π‘₯ + 2 βˆ’ 1 ( π‘₯ + 1 ) 2

Q2:

Consider the rational expression 𝑅 = 5 π‘₯ βˆ’ 3 1 π‘₯ + 3 9 ( π‘₯ βˆ’ 4 ) ( π‘₯ + 1 )   . The following strategy reveals it as a sum of partial fractions.

What is the value of 𝑅 ( π‘₯ βˆ’ 4 )  when π‘₯ = 4 ? Let us call this π‘Ž .

So, 𝑅 = π‘Ž ( π‘₯ βˆ’ 4 ) + 𝑆  . What is 𝑆 ? Give the factored and simplified form.

  • A 𝑆 = 5 ( π‘₯ βˆ’ 2 ) ( π‘₯ βˆ’ 4 ) ( π‘₯ + 1 )
  • B 𝑆 = 5 ( π‘₯ + 2 ) ( π‘₯ βˆ’ 4 ) ( π‘₯ + 1 ) 
  • C 𝑆 = 5 ( π‘₯ βˆ’ 2 ) ( π‘₯ βˆ’ 4 ) ( π‘₯ + 1 ) 
  • D 𝑆 = ( π‘₯ βˆ’ 2 ) ( π‘₯ βˆ’ 4 ) ( π‘₯ + 1 ) 
  • E 𝑆 = ( π‘₯ βˆ’ 2 ) ( π‘₯ βˆ’ 4 ) ( π‘₯ + 1 )

Repeat the first step with ( π‘₯ βˆ’ 4 ) 𝑆 and ( π‘₯ + 1 ) 𝑆 to find 𝑏 and 𝑐 so that 𝑆 = 𝑏 ( π‘₯ βˆ’ 4 ) + 𝑐 ( π‘₯ + 1 ) . What, finally, is the partial fraction decomposition of 𝑅 ?

  • A 3 π‘₯ + 1 + 2 π‘₯ βˆ’ 4 βˆ’ 1 ( π‘₯ βˆ’ 4 ) 
  • B 3 π‘₯ + 1 + 1 π‘₯ βˆ’ 4 βˆ’ 2 ( π‘₯ βˆ’ 4 ) 
  • C 3 π‘₯ + 1 βˆ’ 2 π‘₯ βˆ’ 4 βˆ’ 1 ( π‘₯ βˆ’ 4 ) 
  • D 3 π‘₯ + 1 βˆ’ 1 π‘₯ βˆ’ 4 + 2 ( π‘₯ βˆ’ 4 ) 
  • E 3 π‘₯ + 1 + 2 π‘₯ βˆ’ 4 + 1 ( π‘₯ βˆ’ 4 ) 

Q3:

Determine the partial fraction decomposition of π‘₯ + π‘₯ + 1 π‘₯ ( π‘₯ βˆ’ 3 ) ( π‘₯ + 1 ) 2 2 .

  • A 1 4 ( π‘₯ + 1 ) + 1 1 6 ( π‘₯ + 1 ) βˆ’ 1 3 π‘₯ + 1 3 4 8 ( π‘₯ βˆ’ 3 ) 2
  • B βˆ’ 3 2 ( π‘₯ + 1 ) + 1 1 6 ( π‘₯ + 1 ) βˆ’ 1 3 π‘₯ + 1 3 4 8 ( π‘₯ βˆ’ 3 ) 2
  • C βˆ’ 3 2 ( π‘₯ + 1 ) + 1 1 6 ( π‘₯ + 1 ) + 1 3 π‘₯ βˆ’ 7 1 2 ( π‘₯ βˆ’ 3 ) 2
  • D 1 4 ( π‘₯ + 1 ) + 1 1 6 ( π‘₯ + 1 ) βˆ’ 1 3 π‘₯ βˆ’ 7 1 2 ( π‘₯ βˆ’ 3 ) 2
  • E 1 4 ( π‘₯ + 1 ) + 1 1 6 ( π‘₯ + 1 ) + 1 3 π‘₯ + 1 3 4 8 ( π‘₯ βˆ’ 3 ) 2

Q4:

Find 𝐴 and 𝐡 such that 2 π‘₯ ( π‘₯ βˆ’ 3 ) = 𝐴 π‘₯ βˆ’ 3 + 𝐡 ( π‘₯ βˆ’ 3 ) 2 2 .

  • A 𝐴 = 2 , 𝐡 = 6
  • B 𝐴 = βˆ’ 2 , 𝐡 = βˆ’ 6
  • C 𝐴 = 6 , 𝐡 = 2
  • D 𝐴 = 2 , 𝐡 = βˆ’ 6
  • E 𝐴 = βˆ’ 2 , 𝐡 = 6
Preview